Development of the Sanya Incoherent Scatter Radar and Preliminary Results. Issue 8 (23rd August 2022) - Yue, Xinan; Wan, Weixing; Ning, Baiqi; Jin, Lin; Ding, Feng; Zhao, Biqiang; Zeng, Lingqi; Ke, Changhai; Deng, Xiaohua; Wang, Junyi; Hao, Honglian; Zhang, Ning; et al.
Abstract: Led by the Institute of Geology and Geophysics, Chinese Academy of Sciences, we have built a brand‐new modular active digital phased array, with all solid‐state transmission and digital receiving incoherent scatter radar (ISR) in Sanya (18.3°N, 109.6°E), a station in low latitude China called Sanya ISR (SYISR) since 2015. The development of SYISR involved the indoor design and development of key components, an outdoor prototype test, and the production and debugging of the entire array. The unique features of SYISR include a single‐channel directly connected T/R unit and antenna, a radar array monitoring and calibration network, environmental adaptability design and open architecture. The entire radar has 4, 096 channels and 5, 930 modules in total. All the technical indices, mainly including a >2 MW peak power, a 43 dBi antenna gain and a <120 K noise temperature, either meet or are superior to the designed value through an independent evaluation. Waveforms of single pulse, linear frequency modulation, Barker code, long pulse and alternating code have been implemented to meet multiple purposes. Four observational modes for ionospheric experiments, including zenith stare, perpendicular to geomagnetic field, meridian scan, and all sky scan, have been developed. We have implemented time domain decoding, frequency domain decoding, and statistical inversion methods in calculating the autocorrelation function and power spectra in signal processing. The preliminary experimental results on ionospheric parameters, plasma lines, irregularities and hard targets are reasonable and encouraging, which greatly enhances our confidence in achieving our scientific goals in the future. Plain Language Summary: The Earth's ionosphere (∼60–1, 000 km above the sea level) is composed of dense plasma, which shows complicated variations versus altitude, geographic location, and solar activity level. When a ground‐based radio wave is transmitted onto these plasmas, it will generate stimulated radiation, with a small portion of them radiating back to the ground. If this backscattered radiation is collected by a ground‐based radar, a variety of ionospheric parameters, including plasma density, temperature, and movement speed, can be derived through a complicated signal processing algorithm. An ionospheric monitoring method called incoherent scatter radar (ISR) was therefore developed. However, since this backscattered radiation is very weak, the ISR should be built with sufficiently large power (usually megawatts) and apertures (usually hundreds of square meters). This leads to the high cost of building an ISR, with only a few having been built in the world thus far. In this paper, we describe a newly built ISR, called Sanya ISR (SYISR), in low latitude China by applying modern radar technologies, such as modular active digital phased arrays, all solid‐state transmitting and digital receiving. The development of SYISR followed the principle of a gradual and orderly progress, including indoor design, outdoor prototype testing and the entire radar construction and debugging. The radar technical indices have been evaluated, and all meet the designed value. We also developed a signal processing algorithm and a variety of observational modes. Finally, preliminary experimental results are shown, which are reasonable and encouraging. In the future, we will gradually achieve our scientific goals via effective data accumulation and analysis. Key Points: Sanya incoherent scatter radar (SYISR) is a newly built incoherent scatter radar in low latitude China with modular active electronic scanning, digital phased array, solid‐state transmitting, and digital receiving This paper details the hardware, key parameters, data processing and preliminary experimental results of SYISR The key parameters meet or are superior to the original design, and the preliminary observations are encouraging